2020
DOI: 10.1007/s12038-020-00102-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a repurposed drug as an inhibitor of Spike protein of human coronavirus SARS-CoV-2 by computational methods

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV-2) is an emerging new viral pathogen that causes severe respiratory disease. SARS-CoV-2 is responsible for the outbreak of COVID-19 pandemic worldwide. As there are no confirmed antiviral drugs or vaccines currently available for the treatment of COVID-19, discovering potent inhibitors or vaccines are urgently required for the benefit of humanity. The glycosylated Spike protein (S-protein) directly interacts with human angiotensin-converting enzyme 2 (ACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…Furthermore, previous reports suggest a disagreement between docking Δ G and MM-GBSA Δ G bind determined using Prime module [ 29 , 30 , 31 ]. Many ligands have been shown to bind the RBD of Spike protein with an estimated value of Δ G bind in the range of −21.45 to −54.11 kcal/mol, which is close to our estimated value [ 32 , 33 ]. Interestingly, the Prime/MM-GBSA values of lomitapide, dihydroergotamine mesylate, and olaparib against the Spike protein of SARS-CoV-2 have been estimated to be −98.46, −84.67, and −80.19, respectively [ 34 ].…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, previous reports suggest a disagreement between docking Δ G and MM-GBSA Δ G bind determined using Prime module [ 29 , 30 , 31 ]. Many ligands have been shown to bind the RBD of Spike protein with an estimated value of Δ G bind in the range of −21.45 to −54.11 kcal/mol, which is close to our estimated value [ 32 , 33 ]. Interestingly, the Prime/MM-GBSA values of lomitapide, dihydroergotamine mesylate, and olaparib against the Spike protein of SARS-CoV-2 have been estimated to be −98.46, −84.67, and −80.19, respectively [ 34 ].…”
Section: Resultssupporting
confidence: 87%
“…Of lately, strategy of repurposing of the approved small molecule drugs in order to inhibit SARS-CoV-2 S protein and human ACE2 interaction through virtual screening approaches is used where drugs, Diammonium Glycyrrhizinate, Digitoxin, Ivermectin, Rapamycin, Rifaximin, and Amphotericin B represented the most desirable features to serve as RBD blockers [ 43 ]. Similar other study showed laxative drug, Bisoxatin to have potentials act as RBD blocker [ 44 ]. S-protein is additionally focused with the most ordinarily discovered phytochemicals, where Kaempferol, Quercetin, and Fisetin had been appeared to bind and block the RBD which is validated utilizing molecular docking and MD reenactments [ 45 ].…”
Section: Discussionsupporting
confidence: 74%
“…Assumption of folic acid has been observed to protect pregnant women from SARS-CoV-2 infection, with contrasting evidence suggesting that it may either inhibit the furin protease, needed by the virus to enter the host cell, or the protease 3CL pro , essential for viral replication [ 37 ]. As a small-molecule antiviral agent, tegobuvir has been evaluated in clinical trials for COVID-19 [ 38 ], while bisoxatin (DB09219) has been suggested as a potential inhibitor of SARS-CoV-2 spike protein following a computational approach [ 39 ]. Amodiaquine has been found to inhibit SARS-CoV-2 replication in vitro [ 40 ], ketanserin has been suggested as a potential additive drug to improve the ventilation/perfusion mismatch in patients with COVID-19 [ 41 ] and, finally, the anti-HIV drug raltegravir has been proposed as a potential 3CL pro inhibitor following a computational approach [ 42 ].…”
Section: Resultsmentioning
confidence: 99%